SYVN1-MTR4-MAT2A Signaling Axis Regulates Methionine Metabolism in Glioma Cells - Wang, Lude; Hu, Bin; Pan, Kailing; Chang, Jie; Zhao, Xiaoya; Chen, Lin; Lin, Haiping; Wang, Jing; Zhou, Gezhi; Xu, Wenxia; Yuan, Jianlie (Frontiers in Cell and Developmental Biology, 2021)
Methionine is one of the essential amino acids. How tumor cells adapt and adjust their signal transduction networks to avoid apoptosis in a methionine-restricted environment is worthy of further exploration. In this study, we investigated the molecular mechanism of glioma response to methionine restriction, providing a theoretical basis for new treatment strategies for glioma. Methods We constructed methionine-restriction-tolerant cells in order to study the response of glioma to a methionine-restricted environment. The transcriptome analysis of the tolerant cells showed significant changes in MAT2A. Western blotting, immunohistochemistry, quantitative real-time PCR, colony formation assays, and other experiments were used to verify the role of MAT2A in glioma genesis. In addition, the regulatory mechanism of MAT2A mRNA nuclear export was investigated by transfection, plasma nucleation separation, and co-immunoprecipitation. Results Under methionine restriction, glioma cells showed high expression of MAT2A, and an inhibitor of MAT2A reduced the proliferation of tumor cells. The expression of MAT2A was positively correlated with World Health Organization-grade glioma. High expression of MAT2A was related to increased transfer of its mRNA out of the nucleus. The expression of nuclear export regulatory molecule MTR4 could affect the export of MAT2A mRNA. In a methionine-restricted environment, ubiquitination of MTR4 was enhanced, and thus its protein level was reduced. The E3 ubiquitin ligase was verified to be SYVN1. Conclusion In summary, methionine restriction leads to increased ubiquitination of MTR4, which promotes the transfer of MAT2A mRNA out of the nucleus and MAT2A protein expression. MAT2A promotes histone methylation, prompting cells to proliferate in a methionine-restricted environment.